Turkish newspapers' peace journalism exam: Gezi Park protests - Aluc, Engin; Ersoy, Metin (Springer, 2018)
The basic aim of this study is to explore Turkish newspapers' news coverage of the Gezi Park protests in 2013. These newspapers are published under Dogan Media Group (DMG) conglomerate. The main aim of this study is to examine peace journalism principles in practice in the context of three DMG newspapers. The study examines the news coverage of the protests in order to formulate a peace journalism approach for journalists. Coverage on the protests, the framing analysis was used as a method. Gezi stories have been analyzed from the front pages of newspapers between 29 May and 30 June 2013. In Turkey, many newspapers have distorted the reality, emphasized marginality and did not pass the test of democratic examination while covering protests came to ignore the peaceful actions. However, peace journalism assumption should be used by journalists while covering the peaceful actions or protests. In democratic dispensation, representation of the electorate should continue both in public spheres and in media. The role of the media is becoming more and more important. The media should not only focus on the violence, but should give voice to nonviolence and peace protests as well. Results show that these three newspapers give more voice to former Prime Minister R.T. Erdogan than other official sources and tend to use the voices of elite authorities. This research found that, Posta quoted more elite sources in relation to the protests than Hurriyet and Radikal. At the end of this research DMG's Written Press Publication Principles have been found to have little effect on coverage of newspapers.
Keywords: Turkish newspapers; Peace journalism; News framing; Gezi Park